Energy landscape of polymorphic amyloid generation of β2-microglobulin revealed by calorimetry. Issue 57 (3rd July 2018) - Kinoshita, Misaki; Lin, Yuxi; Dai, Itoh; Okumura, Masaki; Markova, Natalia; Ladbury, John E.; Sterpone, Fabio; Lee, Young-Ho
Abstract : ITC-based energy landscape provides a comprehensive understanding of amyloid aggregation in terms of thermodynamics and kinetics. Abstract : Understanding of amyloid aggregation in terms of thermodynamics and kinetics is still limited. We herein examined the mechanism of β2-microglobulin amyloidogenesis using our unique method of isothermal titration calorimetry-based thermodynamic/kinetic measurements, and revealed the energy landscape of polymorphic amyloidogenesis under biological environment-mimicking conditions including shear forces and crowding effects.